Liquid and Frozen Storage of Agouti (Dasyprocta leporina) Semen Extended with UHT Milk, Unpasteurized Coconut Water, and Pasteurized Coconut Water - W. M. Mollineau; A. O. Adogwa; G. W. Garcia (Veterinary Medicine International)
This study evaluated the effects of semen extension and storage on forward progressive motility % (FPM%) in agouti semen. Three extenders were used; sterilized whole cow's milk (UHT Milk), unpasteurized (CW) and pasteurized coconut water (PCW), and diluted to 50, 100, 150, and 200 × 106 spermatozoa/ml. Experiment 1: 200 ejaculates were extended for liquid storage at 5∘C and evaluated every day for 5 days to determine FPM% and its rate of deterioration. Experiment 2: 150 ejaculates were extended for storage as frozen pellets in liquid nitrogen at −195∘C, thawed at 30∘ to 70∘C for 20 to 50 seconds after 5 days and evaluated for FPM% and its rate of deterioration. Samples treated with UHT milk and storage at concentrations of 100 × 106 spermatozoa/ml produced the highest means for FPM% and the slowest rates of deterioration during Experiment 1. During Experiment 2 samples thawed at 30∘C for 20 seconds exhibited the highest means for FPM% (12.18 ± 1.33%), 85% rate of deterioration. However, samples were incompletely thawed. This was attributed to the diameter of the frozen pellets which was 1 cm. It was concluded that the liquid storage method was better for short term storage.